2013
DOI: 10.2478/pjct-2013-0066
|View full text |Cite
|
Sign up to set email alerts
|

A novel functional MgO ∙ SiO2/polyhedral oligomeric silsesquioxane hybrids as an active filler of polypropylene

Abstract: New organic/inorganic hybrid fi llers were obtained by mechanical modifi cation of magnesium silicate with selected polyhedral oligomeric silsesquioxane and characterized afterwards. MgO • SiO 2 was precipitated in a water system. The effect of chemical modifi cation of magnesium silicate surface on their physicochemical properties was determined. Functionalization was carried out with the use of different amount of (1-(3-hydroxypropyl)dimethylsiloxy-3,5,7,9,11,13,15-hepta(isobutyl)pentacyclo-[9.5.1.1 3,9 .1 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Modification of polymers with silsesquioxanes received a considerable interest among researches nowadays. An influence of POSS additives on thermal, rheological, mechanical, and structural properties of thermoplastics and curable polymeric materials has been investigated . In case of polyolefins, it is proved that small amounts of POSS, less than 1 wt %, rarely lead to significant changes in polymer properties .…”
Section: Introductionmentioning
confidence: 99%
“…Modification of polymers with silsesquioxanes received a considerable interest among researches nowadays. An influence of POSS additives on thermal, rheological, mechanical, and structural properties of thermoplastics and curable polymeric materials has been investigated . In case of polyolefins, it is proved that small amounts of POSS, less than 1 wt %, rarely lead to significant changes in polymer properties .…”
Section: Introductionmentioning
confidence: 99%
“…1), but only a few previous studies have described cage molecules containing 4, 6, 10, or 12 silsesquioxane fragments. By contrast, over 1000 previous studies have reported octameric cage molecules [RSiO 1.5 ] 8 (cubic structures) with different organic groups at the silicon atom [2,[11][12][13][14][15][16][17][18][19][20][21][22] (see Table 1). M a n u s c r i p t 3 This prevalence of octameric structures among structures with the same composition but different sizes is not accidental, and there are several possible explanations.…”
Section: Introduction Of Metal Atoms Into Cage Siloxane Structurementioning
confidence: 69%
“…The filler can be of either natural or synthetic origin and may have a different form [1,2]. Nowadays many researches are also being conducted into the production and application of multicomponent, and thereby multifunctional, fillers (that modify more than one property), so-called hybrid fillers [5][6][7]. Examples of this type of fillers are systems con- 1) Poznan University of Technology, Institute of Chemical Technology and Engineering, Berdychowo 4, 60-965 Poznań, Poland.…”
Section: Zastosowanie Pomiarów Reologicznych Typu In-line W Charaktermentioning
confidence: 99%
“…2) University of Adam Mickiewicz in Poznan, Center for Advanced Technology, Umultowska 89c, 61-614 Poznań, Poland. * ) Author for correspondence: e-mail: Arkadiusz.Klozinski@put.poznan.pl taining polyhedral oligomeric silsesquioxanes (POSS), such as POSS/silica [5], POSS/lignin [6], POSS/MgO•SiO 2 [7], or the system phosphorylated cashew nut shell liquid prepolymer (PCNSL)/kaolin [8]. A hybrid filler, e.g., POSS/silica, not only constitutes a modern multifunctional system, but also allows an expensive filler (a POSS--type nanofiller) to be introduced to the polymer matrix by applying it onto the surface of an inexpensive and readily available carrier, which is silica.…”
Section: Zastosowanie Pomiarów Reologicznych Typu In-line W Charaktermentioning
confidence: 99%